A systematic literature review of resilience approaches in small and medium tourism-based sector - Rohini Shakthinathan; Velan Kunjuraman (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study aims to understand the resilience towards crisis in small and medium tourism-based sectors. The current pandemic has had a particularly detrimental effect on the tourism sector, with COVID-19 posing a significant health threat to the world. This study aims to review and analyses contemporary methods and approaches systematically. To facilitate the integration of multiple research designs in this study, the review was conducted using the published standard (PRISMA statement) as the preferred reporting item for systematic reviews and meta-analyses. The primary databases used in this study were Web of Science and Scopus in order to search for the necessary articles. Through content analysis, this study can be divided into six categories: (a) social support, (b) technology innovation, (c) government support, (d) diversification of economic activities, (e) personal resources and (f) leadership and communication. The findings significantly contribute to the tourism small and medium-sized enterprises in creating resilience-based sustainable tourism, and society’s well-being apart from contributing to the COVID-19 tourism resilience literature. The objective of the study would be to facilitate collaboration between tour operators, government entities and other relevant stakeholders in order to better manage the ambiguity of the COVID-19 crisis and to implement strategies to revitalize the sector in the post-pandemic environment.